STUDI KARAKTERISTIK LALU LINTAS DARI PENERAPAN “CONTRAFLOW” DI JALAN TOL CAWANG – SEMANGGI (STUDI KASUS : ZONA AKHIR) - Makarim, Moh. Fikri; Sumabrata, Jachrizal; Marino, Alan (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Implementation of the contraflow special lane is expected to provide a solution to the lack of road capacity at the inner city highway (Cawang – Semanggi) during peak hour time. This research was conducted to find out and compare the performance  of the characteristics of the traffic flow between two points of observation (middle point and the exit after the contraflow special lane) in order to know the effectiveness of the contraflow lane. This research uses traffic survey by means of recording traffic condition in both points of observation to obtain more accurate traffic characteristic data. The analysis of traffic characteristic performance is conducted by comparing the results of the survey to the traffic parameters of standards from the Indonesian Highway Capacity Manual and regulations from Bina Marga and Jasa Marga as well as the analysis through the relationship of traffic characteristics from Greenshields Theory to assess the traffic performance from both points of observation. The results show that the implementation of the special contraflow lane may decrease the degree of saturation from greater than 0.75 to less than 0.75 by giving the road additional capacity. This shows that the contraflow lane can be considered as an effective and worthy measure to ease the burden of the ever increasing number of cars passing through the toll road during peak hours.